Identifikasi tren penelitian dan peluang inovasi pembelajaran melalui analisis bibliometrik strategi pembelajaran biologi di sekolah menengah - Fajeriadi, Hery; Fitriani, Antung (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Effective learning strategies need to be designed to support in-depth exploration, adapt teaching methods to student needs, and utilize technology and diverse learning resources. This study aims to identify research trends and opportunities for learning innovation through the analysis of biology learning strategies in secondary schools. This research uses a bibliometric study to identify research trends and innovation opportunities in biology learning strategies in secondary schools. The data source is the Google Scholar database for the period 2019-2023 analyzed with the Publish or Perish and VOSviewer applications. Data filtering was carried out based on the keywords “biology learning” “learning strategies” “secondary school”. The results found 579 relevant documents with 5416 citations, 1083.20 citations per year, and 9.35 citations per document. VOSviewer visualization revealed that “teaching,” “technology,” and “problem-based learning” were the main topics, and in recent years there has been a shift towards the use of technology and innovative approaches. Opportunities for innovation in biology learning in secondary schools are still vast, especially technology integration, optimization of problem-based learning approaches, adaptation of online and hybrid models, use of digital platforms, development of self-efficacy, and innovation of learning environments to increase student motivation and engagement in the learning process. The most cited studies show that the development of higher-order thinking skills, the use of technology, and local and problem-based approaches can improve the effectiveness of biology learning strategies in secondary schools. These innovations have great potential to improve student engagement and learning outcomes, providing important guidance for educators in designing effective learning strategies.Strategi pembelajaran yang efektif perlu dirancang untuk mendukung eksplorasi mendalam, menyesuaikan metode pengajaran dengan kebutuhan siswa, dan memanfaatkan teknologi serta sumber belajar yang beragam. Penelitian ini bertujuan untuk mengidentifikasi tren penelitian dan peluang inovasi pembelajaran melalui analisis strategi pembelajaran biologi di sekolah menengah. Penelitian ini menggunakan studi bibliometrik untuk mengidentifikasi tren penelitian dan peluang inovasi dalam strategi pembelajaran biologi di sekolah menengah. Sumber data adalah database Google Scholar periode 2019-2023 dianalisis dengan aplikasi Publish or Perish dan VOSviewer. Penjaringan data dilakukan berdasarkan kata kunci “biology learning” “learning strategies” “secondary school”. Hasil penelitian ditemukan 579 dokumen yang relevan dengan 5416 sitasi, 1083,20 sitasi per tahun, dan 9,35 sitasi per dokumen. Visualisasi VOSviewer mengungkapkan bahwa topik